Neofunctionalization of an ancient domain allows parasites to avoid intraspecific competition by manipulating host behaviour - Jiani Chen; Gangqi Fang; Lan Pang; Yifeng Sheng; Qichao Zhang; Yuenan Zhou; Sicong Zhou; Yueqi Lu; Zhiguo Liu; Yixiang Zhang; Guiyun Li; Min Shi; et al. (Nature Communications, 2021)
Evolutionary arms races can drive adaptations in hosts and parasites as well as among competing parasites. A combination of multi-omics and functional tests identifies a set of genes that allow a parasitic wasp to minimize intraspecific competition by inducing hosts to escape before more wasps can parasitize them.